Induction of tumor cell death through targeting tubulin and evoking dysregulation of cell cycle regulatory proteins by multifunctional cinnamaldehydes. - Amrita A Nagle (Public Library of Science (PLoS), 2012)
Multifunctional trans-cinnamaldehyde (CA) and its analogs display anti-cancer properties, with 2-benzoyloxycinnamaldehyde (BCA) and 5-fluoro-2-hydroxycinnamaldehyde (FHCA) being identified as the ortho-substituted analogs that possess potent anti-tumor activities. In this study, BCA, FHCA and a novel analog 5-fluoro-2-benzoyloxycinnamaldehyde (FBCA), were demonstrated to decrease growth and colony formation of human colon-derived HCT 116 and mammary-derived MCF-7 carcinoma cells under non-adhesive conditions. The 2-benzoyloxy and 5-fluoro substituents rendered FBCA more potent than BCA and equipotent to FHCA. The cellular events by which these cinnamaldehydes caused G(2)/M phase arrest and halted proliferation of HCT 116 cells were thereby investigated. Lack of significant accumulation of mitosis marker phospho-histone H3 in cinnamaldehyde-treated cells indicated that the analogs arrested cells in G(2) phase. G(2) arrest was brought about partly by cinnamaldehyde-mediated depletion of cell cycle proteins involved in regulating G(2) to M transition and spindle assembly, namely cdk1, cdc25C, mad2, cdc20 and survivin. Cyclin B1 levels were found to be increased, which in the absence of active cdk1, would fail to drive cells into M phase. Concentrations of cinnamaldehydes that brought about dysregulation of levels of cell cycle proteins also caused tubulin aggregation, as evident from immunodetection of dose-dependent tubulin accumulation in the insoluble cell lysate fractions. In a cell-free system, reduced biotin-conjugated iodoacetamide (BIAM) labeling of tubulin protein pretreated with cinnamaldehydes was indicative of drug interaction with the sulfhydryl groups in tubulin. In conclusion, cinnamaldehydes treatment at proapoptotic concentrations caused tubulin aggregation and dysegulation of cell cycle regulatory proteins cdk1 and cdc25C that contributed at least in part to arresting cells at G(2) phase, resulting in apoptotic cell death characterized by emergence of cleaved forms of caspase 3 and poly (ADP-ribose) polymerase (PARP). Results presented in this study have thus provided further insights into the intricate network of cellular events by which cinnamaldehydes induce tumor cell death.